Proceedings of the First International Conference on Gameful Design, Research, and Applications 2013
DOI: 10.1145/2583008.2583016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gamification on participation and data quality in a real-world market research domain

Abstract: Gamification has become an increasingly popular way to improve user engagement and motivation, but there is currently a lack of empirical research to demonstrate that increased gamification provides these benefits. To help address this problem we designed three versions of a gamified market research survey and tested them alongside the established industry standard in a study of over 600 participants. We also highlight examples where game elements compromise respondent data, and provide design solutions that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 20 publications
2
52
0
3
Order By: Relevance
“…the badges in GetGlue). Academic research provided successful examples of gamification: Barata et al (2013) showed that introducing points, levels, badges, and leaderboards in an academic course can enhance student involvement and participation; Flatla et al (2011) showed that it is possible to introduce the enjoyable experiences of games in calibration tasks, without drastically transforming the nature of these tasks; and Cechanowicz et al (2013) highlighted that it is possible to obtain greater gamification effects combining different game elements.…”
Section: Hci and Gamificationmentioning
confidence: 99%
“…the badges in GetGlue). Academic research provided successful examples of gamification: Barata et al (2013) showed that introducing points, levels, badges, and leaderboards in an academic course can enhance student involvement and participation; Flatla et al (2011) showed that it is possible to introduce the enjoyable experiences of games in calibration tasks, without drastically transforming the nature of these tasks; and Cechanowicz et al (2013) highlighted that it is possible to obtain greater gamification effects combining different game elements.…”
Section: Hci and Gamificationmentioning
confidence: 99%
“…This is where the majority of past studies failed in combination with relatively small sample sizes [33]. Clearly, there is a lack of empirical research to demonstrate that gamification leads to better results [9]. More precisely, it is unclear if gamification can influence personal (i.e., employee) engagement when employees need to be motivated to share their knowledge inside of the organizational boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…Gamification has been integrated with basic questionnaires and quizzes in academic research, and the results have shown that gamification increases participation level [16]. It was also shown that the process does not negatively affect the quality of the captured data, nor is the performance of the test subjects negatively affected [16].…”
Section: B Gamificationmentioning
confidence: 99%
“…Gamification has been integrated with basic questionnaires and quizzes in academic research, and the results have shown that gamification increases participation level [16]. It was also shown that the process does not negatively affect the quality of the captured data, nor is the performance of the test subjects negatively affected [16]. Not only does gamification increase the fun factor of an application, but it also enables more accurate work, motivates behaviour change [17], enhances retention rate, and is cost effective [18].…”
Section: B Gamificationmentioning
confidence: 99%